2008
DOI: 10.1073/pnas.0803602105
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of Bartonella henselae are counteracted by l -arginine and nitric oxide in human endothelial progenitor cells

Abstract: Microarray analysis indicated several genes involved in immune response were differentially expressed in Bartonella-infected EPCs, whereas these genes returned in steady state when cells were exposed to sustained doses of L-arg. This mechanism may have broad therapeutic applications in tissue ischemia, angiogenesis, immune response, and sepsis.immune response ͉ sepsis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 38 publications
5
49
0
2
Order By: Relevance
“…However, infectious diseases can be detrimental to cardiovascular health not only because they directly promote atherogenesis, but also because they could indirectly contribute to atherosclerosis by reducing the endothelial repair potential of adult stem cells. To address this point we use as a paradigm the recent finding that Bartonella henselae is able to infect EPCs and reduce their number and functionality (Salvatore et al, 2008). Since circulating EPCs play an important role in accelerating endothelization at sites of vascular damage, it is conceivable to hypothesize that the atherosclerotic plaque growth is enhanced and plaque stability is reduced by a spoiled asset of endothelial precursors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, infectious diseases can be detrimental to cardiovascular health not only because they directly promote atherogenesis, but also because they could indirectly contribute to atherosclerosis by reducing the endothelial repair potential of adult stem cells. To address this point we use as a paradigm the recent finding that Bartonella henselae is able to infect EPCs and reduce their number and functionality (Salvatore et al, 2008). Since circulating EPCs play an important role in accelerating endothelization at sites of vascular damage, it is conceivable to hypothesize that the atherosclerotic plaque growth is enhanced and plaque stability is reduced by a spoiled asset of endothelial precursors.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence that Bartonella henselae can infect and damage EPCs reducing the endothelium regenerating potential (Salvatore et al, 2008) might suggest that this infection could increase the risk for CVD. It has been reported that immunocompromised patients, such as those affected by AIDS, receiving organ transplants, under immunosuppressive therapy or affected by Down syndrome (DS), have lower levels of EPCs, reduced angiogenesis and higher risk of CVD (Brouqui & Raoult, 2001;Costa et al, 2010;Dehio, 2001;Harms & Dehio, 2012;Kolb-Mäurer et al, 2002;Mändle et al, 2005;Mosepele et al, 2012;Otsui et al, 2007;Que & Moreillon, 2011;Ryeom & Folkman, 2009;Teofili et al, 2010;Vis et al, 2009).…”
Section: Infected Epcs Uninfected Epcs Epc With Bartonella Invasomementioning
confidence: 99%
See 2 more Smart Citations
“…Aunque los mecanismos no están claramente definidos, se postula que la inhibición de la apoptosis de las células endoteliales, estimulando la producción de factor de crecimiento vascular endotelial 12 y una reprogramación angiogénica de las células infectadas del huésped, pueden actuar como mecanismos con efecto sinérgico entre sí 13 . También se describe que B. henselae se adhiere e invade células hematopoyéticas humanas 14 . Ha sido propuesto que las células hematopoyéticas podrían transportar la bacteria a los tejidos periféricos, en particular, al endotelio de la microcirculación, donde iniciarían los desórdenes vasoproliferativos 2 .…”
Section: Compromiso Por B Henselae De Snc Y Su Relación Con Patologíunclassified